PENGEMBANGAN SISTEM RESERVASI PAKET WISATA KHUSUS CAMPING GROUND DI WISATA ALAM GUNUNG JAE LOMBOK BARAT - Muhamad Hendri Prayegi; I.A.Y.S.D Utami Pidada; Jumraidin (Bajang Institute, 2024)
The purpose of this research is the development of a tour package reservation system, especially Camping Ground in Mount Jae natural attractions in making Camping Ground tour package reservations. West Nusa Tenggara. This study uses descriptive qualitative research methods, namely flexibility in collecting data and deep understanding, with the process of collecting data through observation, interviews, documentation. Primary data was obtained by semi-structured interviews obtained from several informants, namely Bumdes, Pokdarwis and Potential Tourists to find out the development of the Camping Ground tour package reservation system. Skunder data is obtained from various sources such as previous articles related to problems and documentation from photos and tour package flyers. So that the results of this study discuss the theme of the reservation system both customer service excellence, booking, and comfirm. With development through several online and offline media including twitter, instagram, facebook, linkedln, website, whatsapp, gmail, youtube, online travel agent (OTA) and travel agent partners. This research is very important to know and be a reference related to the development of the Camping Ground tour package reservation system in the natural attractions of Mount Jae West Lombok